2012
DOI: 10.1002/rem.21310
|View full text |Cite
|
Sign up to set email alerts
|

Remediating TCE‐contaminated groundwater in low‐permeability media using hydraulic fracturing to emplace zero‐valent iron/organic carbon amendment

Abstract: A field pilot test in which hydraulic fracturing was used to emplace granular remediation amendment (a mixture of zero‐valent iron [ZVI] and organic carbon) into fine‐grained sandstone to remediate dissolved trichloroethene (TCE)‐contaminated groundwater was performed at a former intercontinental ballistic missile site in Colorado. Hydraulic fracturing was used to enhance the permeability of the aquifer with concurrent emplacement of amendment that facilitates TCE degradation. Geophysical monitoring and invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Over time, the guar gel degrades, leaving sand to support the integrity of the facture while allowing for fluids to more easily penetrate through the newly created fracture network (ITRC 2005). Amendments can be incorporated into the fracturing fluid to support in situ remedial technologies (e.g., biodegradation, electrokinetics, vitrification, air sparging) (Suthersan 1999; Swift et al 2012) or can be injected after fracturing into the newly created fracture network (e.g., emulsified zero valent iron [EZVI]) (Quinn et al 2004).…”
Section: Subsurface Access Methodsmentioning
confidence: 99%
“…Over time, the guar gel degrades, leaving sand to support the integrity of the facture while allowing for fluids to more easily penetrate through the newly created fracture network (ITRC 2005). Amendments can be incorporated into the fracturing fluid to support in situ remedial technologies (e.g., biodegradation, electrokinetics, vitrification, air sparging) (Suthersan 1999; Swift et al 2012) or can be injected after fracturing into the newly created fracture network (e.g., emulsified zero valent iron [EZVI]) (Quinn et al 2004).…”
Section: Subsurface Access Methodsmentioning
confidence: 99%
“…The characteristics of emplaced fractures and the distribution of the fractures relative to the contaminant distribution are key features of this approach (Swift et al 2012). For example, Chambon et al (2010) concluded that 0.0025‐cm thick fractures spaced 1 m apart would not be sufficient to ensure site remediation in clayey till through ERD in a reasonable time frame, while Scheutz et al (2010) suggest that 1‐ to 2‐cm thick fractures spaced 0.1 to 0.4 m apart may be sufficient to ensure remediation through ERD in a reasonable time frame.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A variety of pilot‐ or full‐scale fracturing tests have been reported in the literature, and these works can loosely be placed into one of two categories: investigations of fracturing techniques and resulting fracture characteristics (Murdoch et al 2006; Christiansen et al 2008, 2010, 2012; Sorenson 2019), and tests of contaminant treatment with fracturing techniques. The latter category can be divided based on remediation strategy: fractures to promote abiotic degradation through oxidation/reduction reactions (Siegrist et al 1999; Swift et al 2012; Sorenson 2019), fractures to promote biodegradation (Scheutz et al 2010; Swift et al. 2012; Horst et al 2019; Sorenson 2019), fractures for steam flushing (Nilsson et al 2011), or fractures to promote EK treatment (Murdoch and Chen 1997; Roulier et al 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Excavation or soil mixing with remedial amendments (e.g., zero‐valent iron [ZVI] and clay mixing) can be very effective; however, these techniques are invasive, are typically limited to shallow depths, and require relatively lengthy field operations (Horst et al, 2019; Olson et al, 2017). Coupling traditional direct‐push injection techniques with hydraulic or pneumatic fracturing of low‐k media can improve distribution of remedial amendments; however, the unpredictability and inconsistency of induced fractures can hinder treatment effectiveness (Suthersan et al, 2011; Swift et al, 2012). There are other promising technologies for enhanced delivery of remedial amendments in low‐k media, but many remain in early stages of development and require further optimization at the field scale.…”
Section: Introductionmentioning
confidence: 99%